Maternal mortality committee and death surveillance in Recife in improving information: ex-ante and ex-post evaluation - Patrícia Ismael de Carvalho; Suely Arruda Vidal; Barbara de Queiroz Figueirôa; Lygia Carmen de Moraes Vanderlei; Conceição Maria de Oliveira; Cândida Correia de Barros Pereira; José Natal de Figueiroa; Paulo Germano de Frias (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to evaluate the contribution of the Maternal Mortality and Death Surveillance Committee for women of childbearing age (WCA) and maternal mortality in the magnitude of maternal mortality and in the qualification of the causes of death in Recife, Brazil. Methods: ex ante/ex post evaluation, ecological, of the annual indicators of mortality of WCA, maternal and case study of declared maternal deaths according to causes of death before and after surveillance. Deaths of WCA (2010 and 2017) were analyzed. The percentage of investigation of deaths of WCA was calculated; their rates and maternal mortality ratio (MMR) were estimated; the groups of causes of death, classification of death, the moment of death, the proportional variation before and after surveillance, and the relocation of the causes after this process were described. Results: 4.327 (97.0%) of deaths of WCA were investigated (increase of 40.7% of maternal deaths) and MMR of 62.9/100 thousand live births. Improved notifications of immediate/late (75.0%) and remote (300.0%) postpartum; there was a difference in direct obstetric causes, total maternal deaths and late maternal death (p<0.001). Conclusion: the surveillance and the Maternal Mortality Committee showed potential in identifying the magnitude and qualification of causes of maternal death in order to propose the interventions directed to obstetric care.